Behavior of Carbon Fiber Reinforced Concrete Beams. - Germar, Fernando J. (Philippine Engineering Journal)
This test was undertaken for the purpose of demonstrating the increase in load carrying capacity of a plain reinforced concrete beam when reinforced with carbon fiber. A presentation was also made to show the ease with which the carbon fiber reinforcement is applied, something that cannot be said of steel jacketing. With regard to application, carbon fiber reinforcement is a more convenient alternative to the conventional steel jacketing technique for the rehabilitation of aging structures. It weighs substantially less than steel therefore it adds little, if any dead weight to the structure. It is five times stronger and it does not corrode. Deflections are also significantly reduced.